Macro-Mesoscale In-Pile Thermal-Mechanical Behavior Simulation of a UMo/Zr Monolithic Fuel Plate - Kong, Xiangzhe; Jian, Xiaobin; Yan, Feng; Li, Wenjie; Guo, Zixuan; Lu, Chuan; Ding, Shurong; Li, Yuanming (Frontiers in Energy Research, 2022)
UMo/Zr monolithic fuel plates have a promising application prospect in high flux research reactors. To prolong the service life and achieve safety design, the in-pile macro-mesoscale thermal-mechanical behavior of the fuel plate needs further simulation research. In this study, for the fuel meat, the theoretical models of the equivalent fission gas bubble volume fraction, the gas-bubble inner pressure and the maximum skeleton stress are developed, with the effects of bubble distribution pattern involved. The application into the simulation of the in-pile macro-mesoscale thermal-mechanical behavior of the UMo/Zr monolithic fuel plate indicates that the maximum skeleton stress of the fuel meat basically rises with the burn-up, and may reach four times of the macroscale first principal stress of the fuel meat. The distribution patterns of the gas bubbles in the fuel meat might have a distinct influence on the maximum skeleton stress, and the most conservative results of the simple cubic arrangement can be used for the failure prediction of the fuel meat.